Measurements of Microkeratome Cuts in Donor Corneas with Ultrasound and Optical Coherence Tomography - Tang, Maolong (2012)
PURPOSE: To evaluate optical coherence tomography (OCT) in the measurement of donor corneas in preparation for endothelial keratoplasty. METHODS: Donor corneas were imaged by OCT while immersed in preservation medium. Central corneal thickness (CCT) was measured by OCT from Bowman’s layer to the endothelium. The corneas were then mounted on an artificial anterior chamber and the epithelium removed. Ultrasound pachymetry (USP) was used to measure CCT just prior to sectioning with a microkeratome. The central endothelial graft thickness (CGT) was measured by USP. The graft was then return to the medium and imaged by OCT. RESULTS: The study included 154 donor corneas. The average CCT by OCT (550 ± 63 μm) was thicker (p<0.001) than that measured by USP (507 ± 54 μm). Similarly, the CGT by OCT (158 ± 41 μm) was thicker (p<0.001) than that measured by USP (153 ± 38 μm). The predictability of cut depth, as assessed by pooled standard deviation (SD), was better (p=0.023) for USP (41 μm) compared to OCT (48 μm). The graft was thicker (p<0.001) peripherally than centrally in OCT images. The predictability of cut depth by OCT was better (p<0.001) for corneas thinner than 600 μm (SD = 45.6 μm) compared to those thicker than 600 μm (SD = 86.9 μm). CONCLUSION: The donor corneal measurements by OCT were not as predictable as USP. The predictability of graft thickness, however, could be optimized by using OCT to select for corneas thinner than 600 μm, and then using immediate precut USP to set the microkeratome depth. Graft thickness profile measured by OCT could be useful to the surgeon.